Pengaruh Film Series Layangan Putus OTT WeTV Terhadap Minat Penonton Remaja - Fadly Maulana Ibrahim; Muhammad Nuh (Bandung Conference Series: Journalism, 2023)
Abstract. This research is entitled "The Effect of WeTV's OTT Disconnect Kite Film Series on the Interests of Youth Viewers' '. This study aims to determine how much influence the film hasSeries Break KiteTHERE WeTV Against Youth Audience Interests. The theory used in this research is uses and gratifications, in this theory the researcher found significant results in responding to the subject to find out the viewing interest of each individual or group, such as the subjects studied, namely teenagers when using mass media such asOTT WeTv. In this study, researchers wrote using quantitative methods, which aims to determine the extent of influenceSeries Kite SeparatedOOT WeTV on the Interests of Youth Viewers in Grogol Petamburan District. Population in the study amounted to 2,539 people with a sample determination using the Taro Yamane formula with a precision of 10% and a level of trust of 90% until a sample of 100 respondents was obtained. Data collection techniques using questionnaire and observation. Technique Analyze this research data using simple random sampling. The test in this study is based on the statistical T test to find out how far the level of the independent and dependent variables is. to obtain data from this study using the latest SPSS program (version 23) with the Likert scale technique to find out the answers of each respondent. The results of this study obtained 0.809 which shows that Ho has a significance value that is less than 0.05, so H0 is rejected, H1 is accepted, which means that the influence is strong. This means that there is an influence of WeTV's OTT Disconnect Kite Film Series on the Interests of Youth Viewers in Grogol Petamburan District.especially teenagers, to disseminate very important information. The discussion in this study regarding the Kite series is broken because it is a film that is in great demand in OTT WeTv from various countries in 2017, and got positive results. In the research currently being studied, there is a goal, namely how many audiences are interested in watching the kite series breaking up against adolescents in Grogol Petamburan District. The flying kite series film received a positive response from the people of Indonesia and several countries. The theory used in this research uses gratifications, in this theory the researcher found significant results in responding to the subject to find out the viewing interest of each individual or group, such as the subjects studied, namely teenagers when using mass media such as OTT WeTv. By using a quantitative approach method. To see the respondents, researchers used the method probability sampling and purposive sampling through a published questionnaire using google form to find out the results of research on adolescent subjects. Respondents in this study were 100 men and women who live in Grogol Petamburan District aged 17-25th by using the Yamane taro formula, to obtain data from this study by means of the latest SPSS program (version 23) and using the likert scale technique to find out the answers of each respondent. Abstrak. Penelitian ini berjudul “Pengaruh Film Series Layangan Putus OTT WeTV Terhadap Minat Penonton Remaja”. Penelitian ini bertujuan untuk mengetahui besarnya pengaruh Film Series Layangan Putus OTT WeTV Terhadap Minat Penonton Remaja. Teori yang digunakan dalam penelitian ini yaitu uses and gratifications, dalam teori ini peneliti menemukan hasil yang signifikan dalam menanggapi subjek untuk mengetahui minat tonton dari setiap individu maupun kelompok, seperti subjek yang diteliti yaitu remaja saat menggunakan media massa seperti OTT WeTv. Dalam Penelitian ini peneliti menulis dengan menggunakan metode kuantitatif, yang bertujuan untuk mengetahui sejauh mana pengaruh Series Layangan Putus OTT WeTV terhadap Minat Penonton Remaja Kecamatan Grogol Petamburan. Populasi dalam penelitian ini berjumlah 2.539 orang dengan penentuan sampel menggunakan rumus Taro Yamane dengan presisi 10% dan tingkat kepercayaan 90% sehingga diperoleh sampel sebanyak 100 responden. Teknik pengumpulan data menggunakan kuesioner dan observasi. Teknik menganalisis data penelitian ini menggunakan dengan simple random sampling. Pengujian dalam penelitian ini yang didasarkan uji statistik T untuk mengetahui seberapa jauh tingkat variabel independen dengan dependen. untuk mendapatkan data dari penelitian ini dengan menggunakan program spss terbaru (versi 23) dengan teknik skala likert untuk mengetahui jawaban dari setiap responden. Hasil penelitian ini diperoleh 0,809 yang menunjukan Ho memiliki nilai signifikansi yang lebih kecil dari 0,05 maka H0 ditolak H1 diterima, yang berarti pengaruhnya kuat. Artinya terdapat pengaruh Film Series Layangan Putus OTT WeTV Terhadap Minat Penonton Remaja Kecamatan Grogol Petamburan.